Varieties of Non-ordinary Experiences in Brazil—a Critical Review of the Contribution of Studies of ‘Religious Experience’ to the Study of Religion - Schmidt, Bettina E. (International journal of Latin American religions, 2017)
According to the latest national census, 64.6% of Brazilians identified themselves as Roman Catholic. However, the census has little or nothing to do with actual practice or belief. Professing to be a Christian (within any confessional specification) is still part of being Brazilian. But the self-identification does not take into account that religiosity is expressed in very diverse ways nor does it prevent people from believing and practising one of the many Brazilian traditions though identifying themselves as Christian in the census. This perception represents the framework of the following discussion of non-ordinary experiences in Brazil, whether they are perceived as religious, spiritual or ‘just’ extraordinary. This article presents an overview of studies about non-ordinary experiences in Brazil. The aim is to show the importance of these experiences for the understanding of the religious landscape of Brazil.